Clinical and Demographic Profile of Adults with Coronary Artery Anomaly Detected By Computerized Tomography Coronary Angiography - Dangol, Binod; Maskey, Arun; Koirala, Parash; Acharya, Den Prasad; Tiwary, Abhisek; Basnet, Anil (Bangladesh Journal of Medicine, 2026)
Background: The prevalence of coronary artery anomalies (CAAs) varies from 0.2% to 5.6%. Besides conventional invasive coronary angiography (CAG), Computerised Tomography Coronary Angiography (CT-CAG) provides better anatomy of coronary arteries. Early detection and evaluation of coronary artery anomalies is essential because of their potential association with myocardial ischemia and sudden death. We aimed to find the clinical and demographic profile of patients with CAAs and describe pattern of CAAs as detected by CT-CAG at our center. Methods: This cross-sectional study was carried out in the Department of Cardiology, Shahid Gangalal National Heart Centre, Kathmandu, Nepal, from April 2025 to March 2026. The data was collected by analysing the coronary angiographic reports of the patients that underwent CT-CAG. Clinical and demographic profiles of the patients were recorded and CAAs were described using Angelini’s classification. Results: CAAs were found in 84 (40 males and 44 females) of 4081 patients giving a frequency of 2.05%. The mean age was 54.02+11.76 (range 25 - 79). The chest pain was the most common indication for undergoing CT-CAG. Among these, anomalies of origin and course were the most common seen in 69(82.14%) cases. RCA arising from left sinus of Valsalva with interarterial course was the most common anomaly present in 47 (55.9%). LCx arising from RSV was found in 8(9.52%) cases. High take-off of RCAfrom ascending aorta, single ostial origin of both coronary arteries and anomalous origin of left main coronary artery (LMCA) each were seen in 4 (4.76%) cases. Coronary artery aneurysm was seen in 9 (10.71%) cases, while dual LAD was seen in 2 (2.38%) patients, and five (5.95%) cases of coronary cameral fistula were seen. one (1.19%) case each of LCx arising from RCA and LAD arising from RSV were found. Conclusion: We found that the frequency of CAAs was slight female predominance and chest pain being commonest indication for CT-CAG. Though generally asymptomatic some CAAs may produce angina symptoms, myocardial infarction and sudden death. Bangladesh J Medicine 2026; 37(2): 149-155